1998
DOI: 10.1046/j.1525-1594.1998.05092.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Vascular Bed Perfusion with a Polyethylene Glycol‐Modified Hemoglobin‐Encapsulated Liposome, Neo Red Cell, in Rats

Abstract: Whether hemoglobin (Hb) encapsulated liposomes have vasoconstrictive activity remains controversial. We therefore examined the vascular activity of a liposome Hb, Neo red cell (NRC), in a simple in vitro model of Langendorff perfusion of the rat heart using Krebs-Henseleit (KH) solution as the perfusate. In the KH solution, NRC (Hb at 1 mg/ml), however, induced an immediate and abnormal increase in perfusion pressure. Histological examinations revealed that embolisms were the likely cause of this disturbance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…In addition, the metHb level of PEG‐LEHb dispersions can be suppressed by co‐encapsulation of reductants or catalases 33,49,50 . It was also observed that PEG surface modification also improved the biocompatibility, hemodynamic and rheological properties of LEHb dispersions 48,51,52 . In terms of the rheology, LEHb particles PEGylated with DPPE suspended in 5 g/dL of albumin solution exhibited a viscosity of 3.5 cP at 358 s −1 , which is comparable to that of human blood 48 …”
Section: Pehb Dispersionsmentioning
confidence: 86%
“…In addition, the metHb level of PEG‐LEHb dispersions can be suppressed by co‐encapsulation of reductants or catalases 33,49,50 . It was also observed that PEG surface modification also improved the biocompatibility, hemodynamic and rheological properties of LEHb dispersions 48,51,52 . In terms of the rheology, LEHb particles PEGylated with DPPE suspended in 5 g/dL of albumin solution exhibited a viscosity of 3.5 cP at 358 s −1 , which is comparable to that of human blood 48 …”
Section: Pehb Dispersionsmentioning
confidence: 86%
“…and other electrolytes. Moreover, during the long history of the development of Hb-based O 2 carriers (HBOCs) to substitute the function of RBCs, many side effects of molecular Hb have become apparent, such as the dissociation of tetrameric Hb subunits into two dimers (α 2 β 2 → 2αβ), which might induce renal toxicity, and entrapment of gaseous messenger molecules (NO and CO) inducing vasoconstriction, hypertension, reduced blood flow, and impaired tissue oxygenation at microcirculatory levels (Goda et al, 1998;Nakai et al, 1998;, neurological disturbances, and the malfunctioning of esophageal motor function (Murray et al, 1995). These side effects of molecular Hb also imply the importance of the cellular structure of RBC to encapsulate Hb.…”
Section: Development Of Hb-vesicles As a Transfusion Alternativementioning
confidence: 99%
“…229 v. The cellular structure, which resembles that of red blood cells, shields all side effects of molecular Hb, such as scavenging NO and CO (Goda et al, 1998;Nakai et al, 1998;. vi.…”
Section: Hemoglobin-vesiclesmentioning
confidence: 99%
“…Particularly, TRM has a vesicular structure with a lipid bilayer membrane coating its surface with polyethylene glycol as a surface modifier, in which concentrated Hb molecules are encapsulated. This cellular-type Hb possesses some advantages as an artificial oxygen carrier: longer half-life in circulating blood and low vasoconstrictive activity (9,10). Cerebrovascular diseases such as focal or global cerebral ischemia reduce regional blood flow to affected regions, engendering hypoxia/ischemia, which might activate pathogenic cascades and eventual neuronal deficit/ cell damage.…”
Section: Introductionmentioning
confidence: 99%